The Effectiveness of the Constitutionality of the Plan to Change the Threshold of the Election Parliament in the Perspective of Pancasila - Franciscus Xaverius Wartoyo; Ayu Rosita Nugiantari; Hadi Mustopa; Lintang Lasmita Sari; Reinhart Christian (Universitas Syiah Kuala, 2025)
Changes in the parliamentary threshold in the Indonesian election are a crucial issue in the democratic system that has implications for political representation, government stability, and electoral fairness. The Constitutional Court's Decision No.116/PUU-XXI/2023 confirms that the parliamentary threshold of 4% is not fully in line with the principles of people's sovereignty, electoral justice, and legal certainty guaranteed by the 1945 Constitution of the Republic of Indonesia and the values of Pancasila. This study aims to analyze the constitutional effectiveness of changes in parliamentary thresholds and their impact on the electoral system in Indonesia. The research method used is a normative-empirical approach by analyzing the constitutionality of the parliamentary threshold based on legal documents, Constitutional Court decisions, and related legal theories. The results of the study show that the removal of parliamentary thresholds has the potential to increase more proportional political representation, provide opportunities for small and new parties to participate in government, and enrich the diversity of votes in parliament. However, on the other hand, this policy also has the potential to cause political fragmentation that can affect the stability of the government and the effectiveness of legislative decision-making. Therefore, careful policy planning is needed so that these changes remain in line with the democratic principles of Pancasila and do not interfere with legal certainty in the Indonesian electoral system. It is hoped that this research can contribute to policymakers in drafting more inclusive and democratic regulations, while maintaining a balance between the diversity of political representation and the effectiveness of government.